(untitled) - Sinkey, Joseph F. (New York, 1983)
For junior-senior/MBA-level courses in Commercial Banking, Commercial Bank Management, Management of Financial Institutions, Financial Institutions and Markets.A market leader, this thoroughly revised text describes both the theory and practice of commercial banking from a financial-management perspective. Focusing on the dynamic and rapidly changing financial-services industry, it explores modern financial management decision-making and highlights the importance of adapting to change and creating value as the way for firms to succeed.
Keywords: Bank management,Quản trị ngân hàng